29. PERBANDINGAN KEBIJAKAN KOREA SELATAN ERA LEE MYUNG BAK DAN PARK GEUN HYE TERHADAP JEPANG TERKAIT ISU KUIL YASUKUNI SEBAGAI SIMBOL KEJAHATAN PERANG - Harry Fiqri; Tri Cahyo Utomo; Marten Hanura (Journal of International Relations Diponegoro, 2016)
South Korea and Japan are often involve in dynamics relationship which’s effected by thepast issue that bind both of them. That issue is about the existence of Yasukuni Shrine, theshrine became controversy because South Korea believe that the shrine represent Japan’sbrutality during World War II and colonialism were happened. The existence of theTemple stoked tensions and a critcism response from South Korea. Through this issue,South Korea want all of the problem that involve Japan in the past such as ComfortWomen, history text books, and the ownership of Dokdo / Takeshima to be settled. Thepurpose of this study are to compare the foreign policy of Lee Myung Bak and the ParkGeun Hye as the President of South Korea towards the issue of Yasukuni Shrine as asymbol of war crimes. Writer uses neo realism perspective for the theory. For the methodof research writer uses descriptive analytic and qualitative data analysis. The result of theresearch explain the similarity of foreign policy by President Lee Myung Bak andPresident Park Geun Hye and also the difference of foreign policy towards YasukuniShrine Issue as the symbolistic of war crime.